Excessive weight gain onset-age and risk of developing diabetes mellitus: a large, prospective Chinese cohort study - Fang, Wei; Yuan, Xiaojie; Li, Weijian; Seery, Samuel; Chen, Guanzhi; Cai, Zefeng; Huang, Zegui; Wang, Xianxuan; Wu, Weiqiang; Chen, Zhichao; Li, Yan; Wu, Shouling; et al. (Frontiers in Endocrinology, 2023)
Background Excessive weight gain and obesity are widely accepted as risk factors for diabetes mellitus, and the age at which obesity onsets may be related to the development of cardiovascular diseases and certain cancers. Here, we aimed to investigate associations between the onset-age of overweight/obesity and risk of developing diabetes mellitus in China. Methods 42,144 people with the normal weight range and without diabetes at baseline, were enrolled from the Kailuan cohort which began on the 1st June 2006. All participants were followed-up, biennially, until 31st December 2017. During follow-up, 11,220 participants had become overweight/obese. For each case, one normal-weight control was matched according to age ( ± 1 year) and sex. Our final analysis included 10,858 case-control pairs. An age-scaled Cox model was implemented to estimate hazard ratios (HR) with corresponding 95% confidence intervals (CI) for diabetes mellitus incidence across age-groups. Results At a median follow-up of 5.46 years, 1,403 cases of diabetes mellitus were identified. After multivariate adjustments, age-scaled Cox modelling suggested that risk gradually attenuated with every 10 year increase in age of onset of overweight/obesity. Diabetes mellitus adjusted HRs (aHRs) for new-onset overweight/obesity at <45years, 45-54 years, and 55-64 years were 1.47 (95%CI, 1.12-1.93), 1.38 (95%CI, 1.13-1.68), 1.32 (95%CI, 1.09-1.59), respectively. However, new-onset of overweight/obesity at ≥65 years did not relate to diabetes mellitus (aHR, 1.20; 95%CI, 0.92-1.57). This trend was not observed in women or the new-onset obesity subgroup but was evident in men and the new overweight onset subgroup. Conclusion Participants with early onset of excessive weight gain issues are at considerably higher risk of developing diabetes mellitus compared to those who maintain a normal weight.